Effort distribution analysis for the 800 m race: IAAF World Athletics Championships, London 2017 and Birmingham 2018 - López-del Amo, J. L.; Planas-Anzano, A.; Zakynthinaki, M. S.; Ospina-Betancurt, J. (Biomedical Human Kinetics, 2021)
Study aim: To analyse the distribution of effort in the 800 m event at the IAAF World Athletics Championships in London 2017 (outdoor, 44 men, 45 women) and in Birmingham 2018 (indoor, 9 men, 14 women).